2019
DOI: 10.3791/58597
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive, In-pen Approach Test for Laboratory-housed Pigs

Abstract: Traumatic brain injury (TBI) incidences have increased in both civilian and military populations, and many researchers are adopting a porcine model for TBI. Unlike rodent models for TBI, there are few behavioral tests that have been standardized. A larger animal requires more invasive handling in test areas than rodents, which potentially adds stress and variation to the animals' responses. Here, the human approach test (HAT) is described, which was developed to be performed in front of laboratory pigs' home p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For example, in the current experiment, the human observations from the half-and-half pens had lower false positives than the entire population data, especially as pen mates recovered (i.e., days four to six). This finding was not surprising to the authors since previous experiments using continuous measures from repeated human approach tests indicated that compromised pigs will be less responsive and move at a slower pace when a human is standing in front of the pen [45,46]. In the pens that had a mix of compromised pigs and healthy pigs, technicians can directly compare each pig's behavior with their pen mates.…”
Section: Discussionmentioning
confidence: 75%
“…For example, in the current experiment, the human observations from the half-and-half pens had lower false positives than the entire population data, especially as pen mates recovered (i.e., days four to six). This finding was not surprising to the authors since previous experiments using continuous measures from repeated human approach tests indicated that compromised pigs will be less responsive and move at a slower pace when a human is standing in front of the pen [45,46]. In the pens that had a mix of compromised pigs and healthy pigs, technicians can directly compare each pig's behavior with their pen mates.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, the greatest duration of exploratory behaviors were observed near the negative control. For preference research, a negative control is needed to determine if both the positive control and the substrate of interest will be avoided [68]. The refusal volume and exploratory behaviors indicated that the pigs were dissatisfied with the negative control, and avoidance of the blended tea was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…The refusal volume and exploratory behaviors indicated that the pigs were dissatisfied with the negative control, and avoidance of the blended tea was not observed. Exploratory behaviors include NNOB, which in pigs are also referred to in the literature as oronasal or oral-nasalfacial behaviors because pigs also rub their face and root as a part of NNOB [34,68,69]. These behaviors are commonly studied in sows housed in gestation crates that produce a mentally unstimulating environment.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic functional outcome was assessed by the visual–spatial test, human approach test, neurological deficit score, and overall performance category score (for details see Data S1 ). The visual–spatial test was performed to test learning and memory as previously described by Fries et al 19 For evaluating behavior (spatial orientation and activity level in the pen in relation to human presence), the human approach test was performed as described by Hulbert et al 20 The neurological deficit score was used to evaluate neurological function by an animal care taker as previously described. 19 , 21 All tests were performed at the same time of day to account for diurnal rhythm.…”
Section: Methodsmentioning
confidence: 99%